Assessment of animal diseases caused by bacteria resistant to antimicrobials: kept fish species. (2nd February 2022) - ,; Nielsen, Søren Saxmose; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortazar Schmidt, Christian; Herskin, Mette; Michel, Virginie; Miranda Chueca, Miguel Angel; et al.
Abstract: In this Opinion, the antimicrobial‐resistant bacteria responsible for transmissible diseases that constitute a threat to the health of certain kept fish species have been assessed. Atlantic salmon ( Salmo salar ), carp ( Cyprinus spp.), rainbow trout ( Oncorhynchus mykiss ), sea bream ( Sparus aurata ) and tilapia ( Oreochromis spp.), selected as representative of the most important fish species and production systems that are commercially reared in fresh and saltwater farms, were the focus of this assessment. The assessment was performed following a methodology based on information collected by an extensive literature review and expert judgement. Details of the methodology used for this assessment are explained in a separate Opinion. The global state of play of antimicrobial resistance in Aeromonas hydrophila, Aeromonas salmonicida, Flavobacterium psychrophilum and Flavobacterium columnare is provided. Among these bacteria, none was identified as being among the most relevant antimicrobial‐resistant bacteria in the assessed kept fish species in the EU due to the very limited scientific evidence available.